Diagnostic locus for identification of silverside hybrids (Odontesthes humensis and Odontesthes bonariensis) in a natural population - Daiane Machado Souza; Suzane Fonseca Freitas; Rafael Aldrighi Tavares; Heden Luiz Marques Moreira (Boletim do Instituto de Pesca)
Hybridization is a natural phenomenon that occurs more often in fish than in other vertebrates. The use of nuclear and mitochondrial molecular markers provides valuable results in the detection of these events. The aim of this study was to investigate the occurrence of interspecific hybrids in natural populations of silverside. The samples of Odontesthes humensis, Odontesthes bonariensis, and individuals that were morphologically different from pure species were collected in the Mangueira lagoon, located in southern Brazil. Result: Six tetranucleotide microsatellite loci were synthesized and tested. The UFPEL_OH3 locus proved to be diagnostic for the detection of silverside hybrids, and it was possible to distinguish between pure and hybrid species. The mitochondrial marker gene cytb synthesized from conserved Odontesthes sequences in the GenBank genetic database showed no differences in the genetic sequence of the samples, needing further studies to confirm the hypothesis.